Safeguarding from the Sharks: Board Representation in Minority Equity Partnerships - Devarakonda, Shivaram V.; Reuer, Jeffrey J. (Organization Science, 2019)
We study minority equity partnerships and the representation of investing firms on the boards of directors of their partners. In such alliances, an investor firm owns a minority position in the investee partner and may or may not secure a board seat. Prior alliance governance research has largely focused on the choice between equity and nonequity forms of alliances, and it has paid little attention to the particular administrative features of these organizational forms, notably their governing boards. We extend corporate governance research that has emphasized the monitoring and advisory roles of boards by examining how an investee's concerns about knowledge misappropriation can reduce the likelihood that an investor obtains board representation. We suggest that, although there exist opportunities for an investee to benefit from the investor’s advice, the investor's ability to use an investee's knowledge by itself and indirectly with the help of its other partners negatively affects the likelihood of a board seat for the investor. We further argue that this negative effect is amplified when the investee has particularly valuable technologies at risk of appropriation by the investor. Our evidence from minority equity partnerships in the biopharmaceutical industry indicates why and when investors do not obtain board seats, despite the monitoring and advisory benefits that directors can bring to cooperative commercialization agreements.